Human macrophages differentiated in the presence of vitamin D3 restrict dengue virus infection and innate responses by downregulating mannose receptor expression. (2017)
During the last decades, there has been an expansion in the geographic range and incidence of dengue virus (DENV) due to spreading of its mosquito vectors, globalization and the lack of a protective tetravalent dengue vaccine. It is estimated that nearly a third of the world population is at risk of infection with an annual incidence of 96 million symptomatic cases and high economic burden in countries where active DENV transmission has been identified. Infection with DENV may result in a self-limiting febrile illness known as dengue fever with or without warning signs that can progress to severe dengue. Disease severity is hallmarked by hemodynamic compromises that can lead to organ failure, hypovolemic shock and ultimately death. While only a small percentage of cases evolve to severe dengue, progression and severity of dengue disease can differ depending on eco-epidemiology, host genetic factors, age, and virus virulence. Additionally, complex interactions between the host immune response and the virus have been proposed as critical factors contributing to the pathogenesis of the disease In general, upon biting by a dengue-infected mosquito, dermal dendritic cells (DC) and macrophages are the main targets of DENV. In the skin, these cells host viral replication and facilitate further dissemination to peripheral tissues, therefore becoming key drivers in the regulation of DENV-induced immune responses. To initiate infection, DENV has been shown to interact with C-type lectin receptors such as the mannose receptor (MR), Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN) and Ctype lectin domain family 5 member A (CLEC5A) Although MR and DC-SIGN can bind DENV with high avidity facilitating attachment of the virus to the cell, in macrophages,only MR is thought to play a predominant role in virus binding and signaling. Ligation of MR to DENV facilitates spatial interaction of the virus with a lower avidity receptor, CLEC5A [18], which in turn initiates signaling pathways that aim at the secretion of cytokines that potentiate immediate local response and priming of the immune system. DENV-induced activation of target cells is generally believed to induce excessive production of pro-inflammatory cytokines such as TNF-α and IL-1β that affect endothelial integrity and consequently enhance capillary permeability. Furthermore, early in the infection, components of mosquito saliva and local tissue damage at the site of infection cause neutrophils, basophils and mast cells to elicit a Th2 cytokine response with predominant production of IL-4. Notably, the presence of IL-4 induces up-regulation of MR expression on dermal macrophages and recruits monocyte-derived macrophages (MDM), thereby boosting further infection and pro-inflammatory events that may lead to disease progression Currently, no treatment for clinical improvement of dengue disease symptoms is available; however, antiviral and immunomodulatory factors such as vitamin D may have the necessary potential. Apart from its classical role in maintaining calcium homeostasis, vitamin D3 is a potent modulator of the immune system. Indeed, binding of the biologically active form of vitamin D, 1,25-dihidroxyvitamin D3 (vitamin D3), to the vitamin D receptor (VDR) allows the VDR to act as a transcription factor that modulates the gene expression of proteins involved in calcium absorption, cell proliferation and differentiation. Vitamin D3 modulates the immune response to several pathogens including DENV. In fact, epidemiological studies have associated genetic variants in the VDR with disease progression and vitamin D supplementation with early disease recovery. In vitro, vitamin D3 treatment of myelo-monocytic cell lines reduces DENV infection and to modulates the cytokine response; yet the underlying mechanism remains elusive. Therefore, we here investigated the phenotypic features, susceptibility and innate responses to DENV infection of monocytederived macrophages differentiated in the presence of D3 (D3-MDM).